Forecasting Drug Demand Using The Single Moving Average At Prof. dr. I.G.N.G. Ngoerah Hospital - Yuniarti, Endang (Majalah Farmaseutik, 2023)
Problems that often occur in inventory planning are excess and shortages of drug supplies. The single moving average (SMA) forecasting smooths drug demand data fluctuations. This study aims to see the potential and magnitude of errors using the SMA method based on the MAPE values. This research is non-experimental descriptive research. The study sample was the seven highest order drug items based on category A of the ABC analysis results in 2020 and 2021. The sampling technique was purposive sampling using retrospective data. The results obtained were highly accurate forecasting (MAPE <10%) for four drug items, namely Human Albumin 20% Injection 100 mL (MAPE = 2%), Eksemestan 25 mg tablets (MAPE = 3%), Trastuzumab 440 mg/20 mL injection (MAPE = 4%), Deferasirok 500 mg tablets (MAPE = 3%); Good forecasting (MAPE = 10-20%) for one drug item, namely Nilotinib 200 mg capsules (MAPE = 16%), and Reasonable forecasting (20-50%) for two drug items, namely Ifosfamide injection 1 gram (MAPE = 35%), Fentanyl injection 100 mcg / 2 mL (MAPE = 23%) with an average MAPE value of 12%. This study concluded that Prof. Dr. I.G.N.G. Ngoerah Denpasar Hospital could use the SMA forecasting method.